Penerapan Algoritma Genetika Pada Penentuan Lintasan Terpendek Jalur Bus Rapid Transit Makassar - Jusmawati Massalesse (Jurnal Matematika, Statistika dan Komputasi, 2020)
Bus Rapid Transit is a bus system that is fast, convenient, safe and on time from infrastructure, vehicles, and schedules. As a graph problem, BRT representation in a graph is done by assuming the bus stop as a vertex and the distance between bus stops is an edge. The problem examined in this paper is to find out the path that passes through all the bus stops with the smallest total distance, where the trip starts and ends at the same point, and all bus stops are crossed exactly once. The method used is the Genetic Algorithm, which works using objective and fitness functions, and combines selection, crossover and mutation operators to find the best solution. Using the roulette wheel, OX crossover method and a 0.07 of the probability of mutation, the distance of traverse from and to the departure point after passing all bus stops is 19.66 km or 12.22 miles.